Honey in the management of side effects of radiotherapy- or radio/chemotherapy-induced oral mucositis. A systematic review. (February 2019) - Münstedt, Karsten; Momm, Felix; Hübner, Jutta
Abstract: Background: and purpose: In spite of several trials, systematic reviews and meta-analyses, honey is not considered as a viable candidate for the prophylaxis and treatment of radiotherapy-induced oral mucositis in the practice guidelines for supportive care. The purpose of this study was to analyse the value of honey in this treatment situation based on randomized trials acknowledging the fact that manuka honey which is used in some trials distinguishes itself from other honey due to the presence of methylglyoxal. Methods: On the basis of a literature search, we identified and analysed 17 randomized trials on the topic. Participants in these trials received radiotherapy or a combination of radiotherapy and chemotherapy for head and neck cancer. Results: Studies using manuka honey found little rationale for the medicinal use of honey (n = 4) in this field, whereas trials using conventional honey presented data on its usefulness (n = 13). Thus, the type of honey may explain the divergent results of trials in this area. Conclusion: Conventional honey is likely to be effective in the prophylaxis and treatment of radiation- and chemoradiation-induced oral mucositis. Highlights: There is a great controversy regarding the value of honey in the management of side effects of radiotherapy- or radio/chemotherapy-induced oral mucositis. This systematic review found that the majority of the studies on the subject speak in favor of honey. The most important finding is that the type of honey could have influenced the results since all trials with manuka honey failed to show and advantage whereas all studies with conventional honey revealed positive results.